2009
DOI: 10.1007/s11192-009-2236-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of correspondence sections in post-publication peer review: A bibliometric study of general and internal medicine journals

Abstract: Scientific journals claim that correspondence sections are for post-publication peer review. We compared the conditions for submission and the bibliometrics of letters-to-editors published in leading medical journals in 2002 and 2007 using journal-derived information and data from PubMed and Journal Citation Reports. The median time limit for letter submissions decreased from 6 to 3.5 weeks, the median word limit from 400 to 350. The median number of letters per published article was near one in both years. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…The majority of published LTE focused on methodological aspects of the RCT specific to its analysis, intervention and population (Table 3 ). These results support the idea that LTEs can be used as a form of post-publication peer review and that they can play an important role in identifying potential methodological flaws [ 7 , 12 ]. However, only a small proportion of articles undergo substantive criticism in LTE (e.g., a problem that suggest fatal flaws in the design that could invalidate the research) [ 4 , 12 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The majority of published LTE focused on methodological aspects of the RCT specific to its analysis, intervention and population (Table 3 ). These results support the idea that LTEs can be used as a form of post-publication peer review and that they can play an important role in identifying potential methodological flaws [ 7 , 12 ]. However, only a small proportion of articles undergo substantive criticism in LTE (e.g., a problem that suggest fatal flaws in the design that could invalidate the research) [ 4 , 12 ].…”
Section: Discussionsupporting
confidence: 81%
“…Baethge et al conducted a search in Medline in 2007, and found that only 15,312 letters and comments were generated from a total of 117,843 original published clinical articles and reviews [ 12 ]. Furthermore, criticisms are often ignored and undervalued by researchers and clinicians even though they have the potential to shape clinical knowledge [ 4 , 6 , 7 ]. This work also highlights the potential for LTE to be used as a unique knowledge translation tool for journal readers (clinicians and researchers) and editors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study characterizes an exploratory and descriptive research, applying bibliometric analysis (ANURADHA; SHALINI, 2007;QIU;CHEN, 2009;VON ELM et al, 2009) as the research method. Thus, through the specific procedures to be described, it will lead to an overview of the publications about no-tillage from 2006 to 2011.…”
Section: Materials and Methodosmentioning
confidence: 99%
“…• Stringent limits on length and the number of references, which can make it challenging -if not impossible -for experts to explain the issues clearly and convincingly (Altman 2005;von Elm et al 2009). As a result, potential post-publication peer reviewers may decide that a letter to the editor is not an efficient way to raise issues that require attention, and may opt to post a comment on PubPeer.com or a blog instead (Saunders 2011).…”
Section: Pppr: How Hard Can It Be?mentioning
confidence: 99%